Guide to research techniques in neuroscience - Carter, Matt, 1978-; Essner, Rachel; Goldstein, Nitsan; Iyer, Manasi (Academic Press, 2022)
"Modern neuroscience research is inherently multidisciplinary, with a wide variety of cutting edge new techniques to explore multiple levels of investigation. This Third Edition of Guide to Research Techniques in Neuroscience provides a comprehensive overview of classical and cutting edge methods including their utility, limitations, and how data are presented in the literature. This book can be used as an introduction to neuroscience techniques for anyone new to the field or as a reference for any neuroscientist while reading papers or attending talks."--